Perempuan Dalam Tari Galombang Kreasi: Kajian Perubahan Peran Dan Fungsi Terhadap Posisi Penari - Husna Febri Andika Putri; Indrayuda Indrayuda (Populer: Jurnal Penelitian Mahasiswa, 2023)
This study aims to describe and describe 1) the causes of changes in the role and function of dancers' positions by using women in Galombang Kreasi dance. 2) the role and function of female dancers in Galombang Kreasi dance performances. This type of research is qualitative research with descriptive methods. The instrument of this study is the researcher himself and assisted by supporting instruments such as stationery and cameras. Data collection techniques are carried out by means of literature studies, observations, interviews and documentation. The steps of analyzing or analyzing are data reduction, data presentation and inferring data. The results showed that the Galombang Kreasi dance is usually performed by men who can number up to dozens of people and then divided into two groups, where each group seems to be a group of bodyguards. Galombang Kreasi dance has a little element of pencak silat in its movements, so that when it is performed there will be a little martial arts attraction in the series of dances performed, in contrast to pasambahan dance which highlights elegance in every movement and can also be performed by women. The combination of these two dances serves to welcome and pay homage to the bride and groom, also paving the way for a line of virgins carrying carano offerings containing traditional betel. In addition, this new creation of traditional dance also serves as a fence for the entrance of the ninik mamak troupe that accompanies the journey of the bride and groom.